Functional Analysis of Dopaminergic Systems in a DYT1 Knock-in Mouse Model of Dystonia - Song, Chang-Hyun (2012)
The dystonias are a group of disorders characterized by involuntary twisting movements and abnormal posturing. The most common of the inherited dystonias is DYT1 dystonia, which is due to deletion of a single GAG codon (ΔE) in the TOR1A gene that encodes torsinA. Since some forms of dystonia have been linked with dysfunction of brain dopamine pathways, the integrity of these pathways was explored in a knock-in mouse model of DYT1 dystonia. In DYT1(ΔE) knock-in mice, neurochemical measures revealed only small changes in the content of dopamine or its metabolites in tissue homogenates from caudoputamen or midbrain, but microdialysis studies revealed robust decreases in baseline and amphetamine-stimulated extracellular dopamine in the caudoputamen. Quantitative stereological methods revealed no evidence for striatal or midbrain atrophy, but substantia nigra neurons immunopositive for tyrosine hydroxylase were slightly reduced in numbers and enlarged in size. Behavioral studies revealed subtle abnormalities in gross motor activity and motor coordination without overt dystonia. Neuropharmacological challenges of dopamine systems revealed normal behavioral responses to amphetamine and a minor increase in sensitivity to haloperidol. These results demonstrate that this DYT1(ΔE) knock-in mouse model of dystonia harbors neurochemical and structural changes of the dopamine pathways, as well as motor abnormalities.